Seed biopriming with Parachlorella, Bacillus subtilis, and Trichoderma harzianum alleviates the effects of salinity in soybean - Dobyas Maclen Marques da Silva; Cleberton Correia Santos; Fábio Eduardo Wagner; Luiz Otávio Montera Martins; João Pedro Assis Ozório; Obadias Alves da Silva; Dágon Manoel Ribeiro; Silvana de Paula Quintão Scalon (BMC Plant Biology)
Abstract Background Seed conditioning with bioinputs (biopriming) offers a promising and sustainable alternative to mitigate the adverse effects of salt stress on soybeans. This study aims to evaluate the potential of isolated or combined biopriming using microalgae and different microorganisms in alleviating salinity-induced stress in soybeans in early-stage. Methods Seeds were subjected to five biopriming treatments: Parachlorella sp. microalgae culture, Bacillus subtilis, Trichoderma harzianum, Parachlorella sp. + B. subtilis, and Parachlorella sp. + T. harzianum, along with a control group without biopriming. Subsequently, the seeds were exposed to two conditions: (i) control (0.0 MPa), and (ii) salinity induced by NaCl (-0.8 MPa). Germination, photochemical indicators, and seedling performance were assessed. Results Salinity impaired root protrusion and seed physiology, resulting in a high percentage of abnormal seedlings, thus creating a stressful condition. However, biopriming alleviated the negative effects of salinity, particularly with T. harzianum, Parachlorella sp. + B. subtilis, and Parachlorella sp. + T. harzianum, which led to high germination rates and normal seedlings. All biopriming treatments, especially the combined ones, reduced the suppression of non-photochemical quenching, thereby enhancing the maximum yield of photosystem II. Seedlings under salt stress without biopriming exhibited short lengths and low fresh and dry mass, whereas those bioprimed with Parachlorella sp. + B. subtilis and Parachlorella sp. + T. harzianum showed significantly higher values. Conclusion Seed biopriming, especially with Parachlorella sp. microalgae culture combined with B. subtilis or T. harzianum, effectively alleviates the stressful effects of salinity on germination and early-stage growth seedling of soybeans.